Analisis Kualitas Sosial Penduduk di Desa Medan Estate Melalui Angka Harapan Hidup, Pekerjaan (Gaji), dan Pendidikan - Sahala Fransiskus Marbun; Claurisa Tri Milda Purba; Dinda Aprilia; Lajuardi Putra Beheng Sinulingga (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the social quality of the population in Medan Estate Village through three main indicators: life expectancy, employment conditions (salary), and education level. A quantitative approach was used, utilizing demographic and socioeconomic data obtained from relevant agencies and field surveys. The analysis results indicate that life expectancy in Medan Estate Village is in the fairly good category, supported by relatively adequate access to healthcare. However, job quality and income levels remain diverse, with the majority of residents working in the informal sector, which offers salaries below the regional average. The population's education level tends to increase, although intergenerational gaps remain. Overall, this study confirms that the social quality of the community in Medan Estate Village is influenced by the relationship between health conditions, economic capacity, and educational attainment. These findings are expected to inform the formulation of more targeted social development policies.